As reestruturações curriculares do CEFD/UFSM: a história não contada - Fuchs, Marcius Minervini (2016)
This research is in the midst of discussions about educational public policies and formation of physical education teachers. It enters in the discussions of the research line Social-cultural and educational aspects of Physical Education more specifically on teacher training. The study researched how they were created, specifically about teacher training. The study researched how the correlations of strength of actors were given in the processes of curricular restructuring of CEFD/UFSM that resulted in the curricula of 2005 (Degree), 2006 (Bachelor) and 2009 (Constitution of the joint committee for the construction of a formation curriculum only in Degree) from bibliographical study, document analysis and semi-structured interviews. The social actors who were involved in their respective committees of curriculum restructuring were interviewed. The study has as its main objective analyze and document these restructuring processes from the analysis of the correlation of forces of social actors and their roles in the implementation of the educational public policies related to curriculum guidelines or their resistance. In the data analysis it is realized that sectors were structured with proposals of opposing projects that came in a dispute from the beginning. After researching, the constitution processes of the current curricula in vogue, it is raised the hypothesis that these relations were stabilized with agreements, creating a consensus between the parties. In the reunification process the student struggle was the protagonist, however, the majority sector of the teachers managed to use the institutional apparatus to halt the process, which was not approved until the present day. Therefore, CEFD continues with the fragmented training, and the individual interests overcome the the collective interests.